Burden of kidney disease on the discrepancy between reasons for hospital admission and death: An observational cohort study - Shintaro Mandai (Public Library of Science (PLoS), 2021)
Background Physicians have long noted a substantial discrepancy between the reasons for hospital admission and ultimate causes of death, particularly among older adults or patients with complex underlying diseases. However, objective data on this phenomenon are lacking. We aimed to examine the risk of in-hospital death caused by a reason other than the original reason for hospitalization and its association with underlying kidney disease in a nationwide inpatient database. Methods In this retrospective cohort study, we studied 639,556 Japanese adults who died in the hospital from 2012 to 2015, using data from Japan’s Diagnosis Procedure Combination database. We analyzed the discrepancy rate between reasons for hospital admission and death and associated factors using the International Classification of Diseases, 10th Revision (ICD-10) diagnostic codes and seven related categories. Results Among non-chronic kidney disease (CKD) (590,551), CKD (24,708), and end-stage kidney disease (ESKD) (24,297) patients, the median age was 77 years (interquartile range [IQR]: 67–84 years), 83 years (IQR: 75–88), and 75 years (IQR: 67–81), and 25.7%, 30.3%, and 41.6% died from a reason other than the original reason for hospitalization, respectively. Multivariate logistic regression analyses determined CKD/ESKD as the predominant risk factor for this discrepancy, rather than older age, male sex, obesity, and other comorbidities. Sankey diagrams that presented diagnostic changes from hospital admission to death revealed multiple wider segments connecting to different disease classifications, particularly to congestive and septic death in CKD and ESKD patients, respectively. Death owing to another disease classification led to an increase in the median length of hospital stay by 5–7 days and to a 1.3-–1.4-fold increase in medical costs across the populations. Conclusions A substantial proportion of patients with CKD and ESKD died during hospitalization for a reason other than their original reason for admission, leading to increased length of hospital stay and cost.